CODE SWITCHING USED IN A PLAY (BETWEEN COLORED& WHITE PEOPLE) - Bochari, Siska (Kreatif, 2014)
Abstract : Code switching known as the use of two or more languages in conversation has long been a topic of interest in linguistics. Investigation on code switching has been accomplished by many researchers from varied disciplinary backgrounds in a variety of contexts. The objectivesof this article were to describe the type of code switching that occurred in play between black speaker using black English and white speaker employing standard English, to know the factors influencing code switching, and to recognize the type of code choice occurring in that play. Descriptive analysis was used as the method of this article. The data used in this article was from the play entitled FLORENCE which was released in 1950. The characters in the play were colored and white people in Southern America. The result of this article showed that intra-sentential switching dominated the conversation between the colored and white people in that play; situation, participant, and key were factors considered by the speakers in conversation; metaphorical code switching dominated the code choice in that play. Â  Keywords : Code Switching, Intra-sentential Switching, Metaphorical Code Switching